Behçet’s disease in the United States: A single center descriptive and comparative study - Kilian, Nathan C. (Eur J Rheumatol, 2017)
OBJECTIVE: Behçet’s disease is heterogeneous with clinical variability across ethnicities and geographic locations. The goal of this study was to analyze the clinical characteristics of our multi-ethnic Behçet’s disease cohort at the University of Michigan. MATERIAL AND METHODS: A detailed patient characterization was performed. Differences in disease characteristics between men and women, and between patients fulfilling the International Criteria for Behçet’s Disease (ICBD) and the International Study Group criteria (ISG) were determined in our cohort. RESULTS: A total of 114 patients with a male to female ratio of ~ 1:4 were included. All patients met the ICBD criteria, including 76 who also met the ISG criteria. Over 95% of patients had recurrent genital ulcers, which is higher than generally reported. Retinitis was 5.3 times more likely in men than in women (p=0.009), and arthralgia was 3.3 times more likely in women than men (p=0.048). When comparing cohorts derived from the two different criteria, the ISG cohort had more skin manifestations (OR=3.3, p=0.0006). Acneiform lesions were associated with ~8 times higher odds of developing retinitis in our patients (p=0.0008), and superficial thrombophlebitis was associated with a trend for higher odds of developing uveitis (OR=4.1, p=0.057). Using the ICBD criteria, 38 additional patients were identified compared to only using the ISG criteria. Of these patients, 28 presented with only mucosal ulceration with or without joint involvement. CONCLUSION: We characterize Behçet’s disease in a multi-ethnic cohort from North America. Using ICBD criteria in the United States significantly increases the likelihood of identifying Behçet’s disease, particularly in patients with isolated mucosal involvement who constitute a substantial subset of patients in this region.